Integrated Approaches to Occupational Health and Safety: A Systematic Review. Issue 5 (September 2017) - Cooklin, A.; Joss, N.; Husser, E.; Oldenburg, B.
Objective: The study objective was to conduct a systematic review of the effectiveness of integrated workplace interventions that combine health promotion with occupational health and safety. Data Source: Electronic databases (n = 8), including PsychInfo and MEDLINE, were systematically searched. Study Inclusion and Exclusion Criteria: Studies included were those that reported on workplace interventions that met the consensus definition of an "integrated approach, " published in English, in the scientific literature since 1990. Data Extraction: Data extracted were occupation, worksite, country, sample size, intervention targets, follow-up period, and results reported. Quality was assessed according to American College of Occupational and Environmental Medicine Practice Guidelines. Data Synthesis: Heterogeneity precluded formal meta-analyses. Results were classified according to the outcome(s) assessed into five categories (health promotion, injury prevention, occupational health and safety management, psychosocial, and return-on-investment). Narrative synthesis of outcomes was performed. Results: A total of 31 eligible studies were identified; 23 (74%) were (quasi-)experimental trials. Effective interventions were most of those aimed at improving employee physical or mental health. Less consistent results were reported from integrated interventions targeting occupational health and safety management, injury prevention, or organizational cost savings. Conclusion: Integrated approaches have been posed as comprehensive solutions to complex issues. Empirical evidence, while still emerging, provides some support for this. Continuing investment in, and evaluation of, integrated approaches are worthwhile.